Analysis of the Effectiveness of Chicken Egg Distribution in Maintaining Food Price Stability - Shira Raigung Renata; Nisrina Salma Putri; Neng Dinda Septia; Muhamad Nur Amin; Yulianah Yulianah (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study aims to analyze the effectiveness of chicken egg distribution in maintaining food price stability and to identify factors influencing distribution efficiency within the national food system. Research Method: This study employed a qualitative library research approach using content analysis. Secondary data were collected from academic journals, books, and policy reports via Google Scholar, ScienceDirect, SpringerLink, and the Garuda database, using keyword searches, screening, and thematic coding. Results and Discussion: The findings indicate that the distribution of chicken eggs in Indonesia remains inefficient due to long distribution chains, high logistics costs, weak coordination among supply chain actors, unequal market information, and intermediary dominance. Geographic fragmentation and seasonal demand fluctuations also contribute to regional price disparities and food price instability. Implications: The study emphasizes the importance of strengthening logistics infrastructure, institutional coordination, market transparency, and digital distribution systems to improve food price stability. Originality: This study integrates perspectives on distribution effectiveness, supply chain coordination, intermediary structures, and value chain inequality within a single analytical framework.